2000
DOI: 10.2337/diabetes.49.12.2160
|View full text |Cite
|
Sign up to set email alerts
|

Native and modified LDL activate extracellular signal-regulated kinases in mesangial cells.

Abstract: Glycation and/or oxidation of LDL may promote diabetic nephropathy. The mitogen-activated protein kinase (MAPK) cascade, which includes extracellular signal-regulated protein kinases (ERKs), modulates cell function. Therefore, we examined the effects of LDL on ERK phosphorylation in cultured rat mesangial cells. In cells exposed to 100 µg/ml native LDL or LDL modified by glycation, and/or mild or marked (copper-mediated) oxidation, ERK activation peaked at 5 min. Five minutes of exposure to 10-100 µg/ml native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 48 publications
(61 reference statements)
5
41
1
Order By: Relevance
“…This is consistent with our earlier findings demonstrating that HOG-LDL is significantly more cytotoxic than G-LDL [13] and demonstrating a distinct pattern of global gene expression induced by HOG-LDL, but not by G-LDL, in human retinal pericytes [16]. Our group has reported that uptake of HOG-LDL in rat mesangial cells mainly occurs via scavenger receptors, whereas N-and G-LDL are taken up by the LDL receptors [18]. Whether the differential actions of HOG-and G-LDL can be explained by their separate receptor mechanisms is not known.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This is consistent with our earlier findings demonstrating that HOG-LDL is significantly more cytotoxic than G-LDL [13] and demonstrating a distinct pattern of global gene expression induced by HOG-LDL, but not by G-LDL, in human retinal pericytes [16]. Our group has reported that uptake of HOG-LDL in rat mesangial cells mainly occurs via scavenger receptors, whereas N-and G-LDL are taken up by the LDL receptors [18]. Whether the differential actions of HOG-and G-LDL can be explained by their separate receptor mechanisms is not known.…”
Section: Discussionsupporting
confidence: 81%
“…The protein content of LDL was determined using a bicinchoninic acid assay kit (Pierce, Rockford, IL, USA). Native and modified LDLs were characterised by agarose gel electrophoresis (LIPOEPG; Beckman, Fullerton, CA, USA), fluorescence at 360 nm excitation and 430 nm emission (Gilford Fluorimeter IV, Oberlin, OH, USA) and absorbance at 234 nm in a Beckman DU650 spectrophotometer, confirming that the products were of a quality comparable with that in previous reports [18].…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…The small molecule sunitinib is a potent multi-targeted receptor tyrosine kinase inhibitor (O'Farrell et al 2003, Sun et al 2003, suggesting that changes in intracellular signaling pathways are able to modulate the HSD3B2 transcription rate. Studies in respectively cultured mesangial cells (Jenkins et al 2000) and osteoblasts (Klein et al 2006) have indicated that exposure to native LDL -the normal substrate of the LDLR -increases the activity (phosphorylation state) of MAPK and tuberin and lowers Src protein levels and Akt activity. These combined findings suggest that, by changing the activity of major intracellular signaling pathways, enhanced adrenal uptake of native LDL from the plasma compartment might ultimately decrease the HSD3B2 expression in this tissue.…”
Section: Ldlr-ldlr+mentioning
confidence: 99%
“…Mildly glycated LDL cause injury to retinal capillary endothelial cells and pericytes [17]. In cultured mesangial cells, glycated LDL activate extracellular signal-regulated protein kinases 1 and 2, an early mitogenic signal [18]. However, the possible influence of glycated LDL, in vivo, at the level of microvessels remains unknown.…”
Section: Ops Imaging Technologymentioning
confidence: 99%